OSH Monitoring: A Review of Current Research. - Goh Y.M. (2018)
Research on the effectiveness of prevention measures at the workplace : colloquium of the ISSA International Section for Research on Prevention ; 15 and 16 October 2009, Institute Work and Health (BGAG), Dresden, Germany